KARAKTERISTIK PENDERITA HIV/AIDS DI RSUD DR. DJASAMEN SARAGIH PEMATANGSIANTAR TAHUN 2013–2014 - janni togumaito; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT AIDS (Acquired Immune Deficiency Syndrome) is specific illness (syndrome) collecting caused by damaging immune system which is related to HIV (Human Immunodeficiency Virus). Prevalance rate of AIDS in Indonesia in 2014 was 23,48 with CFR of AIDS was 1,67. The main purpose of this research is to know characteristic of HIV/AIDS patients.This research is descriptive study with case series design. The population and sample was all HIV/AIDS patients as many as 145 cases. Type of data collected is secondary data which is analyced by chi square-test. The result of research showed the characteristic based on highest demograhy social with the age 30-39 years (49,0%), male (72,4%), Senior High School passed (55,2%), enterpreuner (53,1%), married (66,9%), Pematangsiantar Living (57,9%), highest infection transmission of heterosexual (65,5%), Clinic with no opportunity Infection (OI) (54,5%), Tuberculosis as OI type (48,5%), number of CD4<200 (60,0%), stop therapy phase (64,1%), alive living (76,6%). It is faound that no significant and different proportion between age and infection transmission (p=0,372), sex and last living (p=0,297), work status and infection transmission (p=0,172), marrige status and infection transmission (p=0,190). There is significant difference proportion between sex and infection transmission (p<0,001), and also clinic and last living (p<0,001). It is suggested for society to be faithful to one person as living mate to prevent transmission through heterosexual in promiscuity, to public figure especially to public religion to get involved in morality education for education for society. It is suggested for staff of HIV/AIDS Poly clinic to monitor patient obedience in consuming ARV and to record information more detail about type of opportunity infection of patients. It is suggested to local government to close prostitution place in Bukit Maraja. Keywords: Characteristic, HIV/AIDS